2017
DOI: 10.1103/physrevd.96.084040
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic stars in Starobinsky gravity with the matched asymptotic expansions method

Abstract: We study the structure of relativistic stars in R + αR 2 theory using the method of matched asymptotic expansion to handle the higher order derivatives in field equations arising from the higher order curvature term. We find solutions, parametrized by α, for uniform density stars. We obtain the mass-radius relations and study the dependence of maximum mass on α. We find that Mmax is almost linearly proportional to α. For each α the maximum mass configuration has the biggest compactness parameter (η = GM/Rc 2 )… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Indeed, the compactness and curvature of a typical NS of mass M = 1.4 M and radius R = 10 km, respectively, are 10 5 and 10 14 times larger than the values probed in solar system tests [33] but they still are in an unexplored regime in the bulk of the NS [27]. There is considerable effort [22,26,[34][35][36][37][38][39][40][41][42][43][44][45][46] to study the mass-radius relation of NSs in modified theories of gravity. In this paper we seek to determine the form of the mass-radius relations for NSs in the EMSG theories in order to determine whether this theory can survive confrontation with observations of NS environments for a selection of four realistic equations of state.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the compactness and curvature of a typical NS of mass M = 1.4 M and radius R = 10 km, respectively, are 10 5 and 10 14 times larger than the values probed in solar system tests [33] but they still are in an unexplored regime in the bulk of the NS [27]. There is considerable effort [22,26,[34][35][36][37][38][39][40][41][42][43][44][45][46] to study the mass-radius relation of NSs in modified theories of gravity. In this paper we seek to determine the form of the mass-radius relations for NSs in the EMSG theories in order to determine whether this theory can survive confrontation with observations of NS environments for a selection of four realistic equations of state.…”
Section: Introductionmentioning
confidence: 99%
“…The authors showed that it is possible discriminate modified theories of gravity from General Relativity due to the gravitational redshift of the termal spectrum emerging from the surface of the star. In [23], a stellar structure model in f (R) = R + αR 2 theory was considered, using the method of matched asymptotic expansion to handle the higher order derivatives in field equations. Solutions were found for uniform density stars matching to the Schwarzschild solution outside the star.…”
Section: Introductionmentioning
confidence: 99%
“…In the Starobinsky model, the interior solutions of relativistic stars also depend on the value of the Ricci scalar [13] as well as the vacuum solutions. The problem being non-well posed prevents finding unique solutions.…”
Section: Discussionmentioning
confidence: 99%